2015
DOI: 10.3892/mmr.2015.3247
|View full text |Cite
|
Sign up to set email alerts
|

Circadian gene hClock enhances proliferation and inhibits apoptosis of human colorectal carcinoma cells in vitro and in vivo

Abstract: Colorectal carcinoma (CRC) is one of the most prevalent types of malignancy-associated mortality worldwide. Previous studies have demonstrated that amplification and overexpression of the human circadian locomotor output cycles kaput gene (hClock) was closely associated with a high risk for CRC as well as poor prognosis in CRC patients. However, the underlying molecular mechanisms of CRC remain to be fully elucidated. In the present study, hClock was exogenously overexpressed in the CRC cell line SW480 via inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…For instance, human colorectal cancers often show higher expression of Clock or Bmal1 genes compared to healthy tissue [112,113,114]. In agreement with this, overexpression of CLOCK increases proliferation of colorectal carcinoma cells in vitro and in vivo [115]. Another study reports elevated levels of CLOCK in ERα-positive breast tumor samples.…”
Section: Does the Circadian Clock Support Tumorigenesis?mentioning
confidence: 82%
“…For instance, human colorectal cancers often show higher expression of Clock or Bmal1 genes compared to healthy tissue [112,113,114]. In agreement with this, overexpression of CLOCK increases proliferation of colorectal carcinoma cells in vitro and in vivo [115]. Another study reports elevated levels of CLOCK in ERα-positive breast tumor samples.…”
Section: Does the Circadian Clock Support Tumorigenesis?mentioning
confidence: 82%
“…Furthermore, upstream regulators may play a role in modulating tumor-suppressive potential of CLOCK and BMAL1, as studies have shown that the unfolded protein response induces a phase shift in circadian oscillations via direct regulation of miR-211 to suppress Clock and Bmal1 expression impacting tumor progression (32). While these preliminary studies indicate that Clock and BMAL1 may serve tumor suppressor-like functions, exceptions exist in colorectal cancer, wherein Clock and Bmal1 expression is elevated, and modeling studies linked high CLOCK expression to increased proliferation (33,34). In addition, in acute myeloid leukemia (AML), Clock and Bmal1 are required for growth of AML (35).…”
Section: Circadian Clock Regulationmentioning
confidence: 99%
“…We found that Tiron could effetely suppress cell autophagy and restore cell viability. It has been shown that CLOCK was found to be significantly increased in gliomas and colorectal carcinoma [32, 33]. ROS levels were also increased in many cancers.…”
Section: Discussionmentioning
confidence: 99%